Etudes philologiques sur quelques langues sauvages de l'Amérique - Cuoq, J. A. (Jean André), 1821-1898.; Du Ponceau, Peter Stephen, 1760-1844. Système grammatical des langues de quelques nations Indiennes de l'Amérique du Nord.; Schoolcraft, Henry Rowe, 1793-1864. (Montréal : Dawson, 1866)
Reproduction of original in: Library of the Public Archives of Canada. In the first part of the book, Cuoq critiques several works of Schoolcraft and Du Ponceau's Système grammatical des langues de quelques nations indiennes de l'Amérique du Nord. Attributed to J.A. Cuoq--National union catalog pre-1956 imprints. Half title: Langues sauvages d'Amérique. Includes bibliographical references. Mode of access: Internet.